Analisis Lentur Balok Penampang T Berlubang Memanjang Menggunakan Metode Elemen Hingga Non-linier - Praganif Sukarno; Muslikh "."; Djoko Sulistyo (Semesta Teknika, 2011)
Numerical analysis is a time-, cost- and equipment-effective method to study the behavior of structures. ATENA is one of the available software-based on finite element method. Hollow cross section is one way to reduce the weight of concrete beam. The effect of holes on beam may reduce the bending resistance. The hollow beam was numerically modeled which and subsequently analyzed using the ATENA v.2.10 software. Material parameters being used as input data was obtained from laboratory tests, assuming that steel-concrete bond was prefect, and and the steel reinforcement was modeled as discrete. The results of numerical analysis of the ATENA were then compared with experimental test results on the flexural behavior and serviceability limit state of reinforced concrete hollow beams lengthwise (Amir, 2010), then study the variation of quality parameters of concrete and the hole size variations. The results shows that the collapse load of hollow beam reached only 96.71% and deflection reached 135.96%. Stiffness of hollow concrete beam was also showed a higher stiffness of the experiment. The crack pattern is flexural fracture and very much agree with that of the experiments. Test parameters of concrete quality variations as well as the hole size variation showed higher concrete quality/size of the hole will reduce the ductility of beam.